Reception and health education in waiting room: evaluation of actions contributiontopediatric dentistry attendance - Emmi, Danielle Tupinambá; Pires, Mariana Jéssica Mafra (Journal of Health Care, 2016)
Objective: Identify how activities in the waiting room contribute to the child’s conditioning before dental treatment, assessing the caregiverunderstanding of oral health knowledge,children’s understandingof oral hygiene habits, empathy with the dentist and the involvement in the proposed activities and their behavior during consultation.Material and Methods: This cross and observational study was conducted in the period fromMarch 2015toJune 2015 and evaluated 30 children that awaited for dentalcare in the Integrated Children’s Dental Clinic of a public college in thenorthern region ofBrazil. Children and caregivers answered a questionnaire concerningoral healthknowledge and empathy inthe dentist-patient relationship. Afterwards they participated in educational activities carried outin the waiting room bythe student responsibleand assessed their involvement in the activities. Then, the student responsible for clinicalcarewas questioned about the child’s behavior during the dental appointment. RESULTS: There is a lack of basic oral healthknowledge , demonstrated by the majorcomplaints of caregiverswhenseeking dental care for children:an installed pathology (66.7%), use of shared tooth brush (6.7%) and non-use of dental floss (66.7%). Most children (96.6%) showed satisfactory involvement in activities and peaceful behavior (80.0%) during clinical care. Conclusion: playful oral health promotion activities can contribute to the acquisition of knowledge by children and caregivers,giving them greater self-careautonomy , and contributingto a less stressful and more collaborative behavior during dental treatment.